Pengaruh Kualitas Produk Dan Citra Merek Terhadap Keputusan Pembelian Motor Matic Yamaha Mio Pada Dealer Jg Dawuan - Haidar Abdul Afif; Nelly Martini (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine the effect of product quality and brand image on purchasing decisions for Yamaha Mio Matic motorcycles at JG Dawuan. The method used is descriptive and verification. The population of this research is the Yamaha Mio Matic Club Bekasi community, the number of which is 153. The determination of the sample is determined by the slovin formula so that the sample taken is 110 respondents. The sampling technique used is random sampling/probability using simple random sampling technique. The type of data used in the study is Primary Data which is data obtained directly from the results of interviews, observations and questionnaires. This study uses a Likert scale, the data analysis technique used to determine the effect in this study is the multiple linear technique with SPSS software. The results of this study indicate that product quality and brand image have a strong and direct relationship, and there is a simultaneous influence of product quality and brand image on purchasing decisions. There is a significant effect of product quality variables on purchasing decisions and there is a significant influence of brand image variables on purchasing decisions. Keywords: Product Quality, Brand Image, Purchase Decision Yamaha Mio Matic